Contribution of different sectors to developed countries' fulfillment of GHG emission reduction targets under the first commitment period of the Kyoto Protocol. Issue 61 (July 2016) - Liu, Shuo; Wilkes, Andreas; Li, Yu'e; Gao, Qingzhu; Wan, Yunfan; Ma, Xin; Qin, Xiaobo
Highlights: GHG emissions for the countries during the first commitment period of the Kyoto Protocol are accounted. GHG emission reductions for each of the countries across six sectors are calculated. Mitigation efforts in different countries between different sectors are compared. The study showed that the energy sector contributed the highest GHG emission reductions, with agriculture and LULUCF sectors played an auxiliary role. Abstract: Greenhouse gas (GHG) data submitted in April 2014 on land use, land use change and forestry (LULUCF), energy, industrial processes, solvents and other product use, agriculture, and waste for 37 developed countries was analyzed to estimate the relative contributions of different sectors to GHG emission reductions. This GHG data from the first commitment period of the Kyoto Protocol included 35 parties to Annex B of the Kyoto Protocol, the United States and Canada. Results show that the contribution of each sector was, in order: energy (36.9%), industrial processes (12.4%), agriculture (9.9%), LULUCF (7.7%), waste (3.4%), and solvents and other product use (0.1%). The average proportion of base year emissions reduced in each sector by countries in Annex B was, in order: energy (7.4%), agriculture (2.7%), LULUCF (1.9%), industrial processes (1.2%), waste (0.5%), and solvents and other product use (0.1%). Overall, the energy sector contributed the highest GHG emission reductions, while the agriculture and LULUCF sectors also made contributions. Most countries achieved limited absolute GHG reductions from their chosen LULUCF activities, but the relative contribution of GHG emission reductions from LULUCF was significant but small. This suggests that, unless there are substantial changes to accounting rules, future emission reductions will mainly result from mitigation actions targeting fossil fuel consumption, while the agriculture and LULUCF sectors will continue to play auxiliary roles.